Examining fisherman perception towards climate change impacts and fishery agencies - Man, Norsida; F., Mohd Fauzi; Y., Muhammad Aliff (Human Resource Management Academic Research Society, 2018)
Fish product is one of the contributors for balance diet, profit and attraction for tourist. That is why today fishery farming have become important in human daily life. Fishing and aquaculture sector have been reported to employ over 36 million people directly, this show the importance of fishery sector. Regardless of this fact, climate change have become the result for fishery farming to gain low income due to low quantity of fishing. In order to face climate change impact, there are several government agencies such as Fishery Department and LKIM that involve with fishermen which can assist them to adapt with the risks and issues in climate change. This research aims to understand the perception level of respondents toward climate change impact and to identify the role of government agencies’ extension activities toward climate change adaptation. This research was conducted in Pekan, Pahang with participation of 150 fishermen as respondents. The result shows the perception of respondents towards extension agent’s organisation and activities are high. It is also recorded that the perception of extension service toward climate change is on high level.